In-Silico Prediction of Oral Drug Bioavailability: A multi-boluses approach. (December 2021) - Cacace, Filippo; Menci, Marta; Papi, Marco; Piemonte, Vincenzo
Highlights: Aim of our model: overcame the limitations of physiological pharmacokinetics models of the literature, introducing a more realistic modeling approach. Discrete-continuous approach: a sequence of boluses travelling in the investigated portion of the intestine, in counter-current with blood. Simulation results: excellent correlation between the predicted and experimental concentration profile. Our approach provides a simple tool, with a good reliability, to analyze a very complex phenomenon, using only few parameters. Abstract: This work focuses on a new mathematical model able to describe in a simple manner the intestinal physiology, in order to better study drug absorption and bioavailability. The aim of our model is to overcome the limitations of physiological pharmacokinetics models of the literature, introducing a different modelling approach. The core of the new proposed model is a Discrete-Continuous Approach (DCA): a sequence of boluses travels in the investigated portion of the intestine, in counter-current with blood that flows in continuous mode. No empirical equations are implemented in this model. Simulation results show an excellent correlation between the predicted and experimental concentration profile used to validate our model. Our new approach provides a simple tool, with a good reliability, to analyze a very complex phenomenon, using only few parameters.